PENGARUH PENERAPAN SELF AFFIRMATION TERHADAP PENURUNAN BODY DISSATISFACTION PADA REMAJA AKHIR - Andika Siswoaribowo; Muhammad Taukhid; Dellia Paramita (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2020)
The desire to appear perfect was more experienced by women’s. Various attempts to look beautiful and attractive, when expectations and efforts are inappropriate with reality it will cause dissatisfaction or Body Dissatisfaction. Self Affirmation is one of the strategies to restore a satisfaction or self-esteem and increase self-awareness so as not to compare herself. This study was aimed to determine the effect of applying Self Affirmation to reducing Body Dissatisfaction in adolescents. The design of this research was used a quasi-experimental within approach pre-test post-test with control group design and used purposive sampling method, which obtained 56 respondents who divided into treatment groups (n=28) and control groups (n=28). This research was carried out 3 times in 1 week by measuring Body Dissatisfaction before giving intervention on the 1st day (pre-test) and after giving the last intervention on the 3rd day (post-test). The results of the analysis used Mann Whitney test showed that Pv=0.000 (Pv<α=0,05), meaning that there were an effect of the applying Self Affirmation to decrease Body Dissatisfaction. The factor that has the most influence is social media, because media more accentuating the physical beauty with a slim body and brighter skin, especially in this modern era social media users are most dominated by adolescents. So it will be easy for adolescents to feel dissatisfied with their body or has been called Body Dissatisfaction. In conclusion, Self-Affirmation reduces Body Dissatisfaction in a person.